2018
DOI: 10.1021/acs.iecr.8b04813
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Hydrofluoroolefins with the Cubic Plus Association and Perturbed-Chain Statistical Associating Fluid Theory Equations of State

Abstract: Hydrofluoroolefins (HFOs) have been proposed as promising candidates for alternative refrigerants. In this work, a comprehensive comparison of the performance of the Cubic Plus Association (CPA) and (perturbed-chain statistical associating fluid theory) (PC-SAFT) equations of state for six thermodynamic properties of HFOs is presented, in which 11 parameter estimation methods are considered and analyzed. On the basis of the comparison with experimental data and a theoretical analysis, a method meeting both sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 56 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…At the same time, other studies have demonstrated accurate modeling of halocarbon systems using various Cubic and SAFT-type EoSs while neglecting such interactions. In this respect, a very important investigation was recently made by Kang et al These authors have performed a fundamental comparison of PC-SAFT and Cubic-Plus-Association (CPA) models, while fitting their parameters to various databases covering different thermodynamic properties of hydrofluoroolefins. They have concluded that although addition of the association term improves modeling of heat capacities, it deteriorates accuracy in estimating other properties.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, other studies have demonstrated accurate modeling of halocarbon systems using various Cubic and SAFT-type EoSs while neglecting such interactions. In this respect, a very important investigation was recently made by Kang et al These authors have performed a fundamental comparison of PC-SAFT and Cubic-Plus-Association (CPA) models, while fitting their parameters to various databases covering different thermodynamic properties of hydrofluoroolefins. They have concluded that although addition of the association term improves modeling of heat capacities, it deteriorates accuracy in estimating other properties.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, novel EOS such as perturbation EOS (such as PC-SAFT) and cubic plus association EOS (CPA) have also been proposed for alternative refrigerants R1233zd(E), R1234yf, R1234ze(E), and R1234ze(Z) [18]. PC-SAFT is Helmholtz free energy-based and its calculation for isobaric heat capacity follows the same process with FEOS, while CPA is pressure-based, adding an association part to traditional cubic EOS.…”
Section: Isobaric Heat Capacity Prediction Methodsmentioning
confidence: 99%
“…A general approach to address the degenerate parameter problem is to include one or more properties in addition to saturated liquid density and vapor pressure data for parameter estimation. Thermodynamic properties such as speed of sound, second virial coefficient, enthalpy of vaporization, and heat capacity can be included when parameterizing both nonassociating and associating systems. , Practical challenges with this approach include the availability of experimental data as well as assigning weights to each additional property in the objective function. Strategies are available to guide the optimal selection of weights (Pareto optimal solutions visualized on a Pareto front), but these techniques have not yet been widely applied to parameterizing thermodynamic models. , …”
Section: Applied Thermodynamicsmentioning
confidence: 99%